Ramkheri 1955 - Jamgod 1990: Von der Kasten- zur Klassengesellschaft? Sozialgeographische Veränderungen in einer Malwa-Gemeinde - Bronger, Dirk (ERDKUNDE, 1991)
We owe to the fifties in particular a good number of detailed village studies in India enabling us to gain a deeper insight into the village life with particular reference to the caste system, unique and characteristic for this country. U p to now, however, there is a very limited number of studies analysing the changes regarding the social and economic structure within the same village over a period of time. This precisely is the target of this paper: using the results of MAYER'S excellent study of the Ramkheri village (used as a pseudonym for its real name of Jamgod) in Central lndia from 1955, the social changes since then are analysed here. The starting point was the controversial discussion as to whether the caste system is breaking down and has thus changed its nature or whether, on the contrary, caste has to be viewed as a stable system allowing no change or very little change during the past decades. For an assessment, and to answer these questions, the changes regarding the interdependencies of the population development, settlement pattern, hierarchical system, landownership, occupational structure and, last but not least, the political leadership on one side and the caste system on the other since 1955, were studied. The analysis comes to the conclusion that only marginal changes in the system itself could be observed during the past 35 years. The changes refer mainly to the occupational structure where gradual mobility could be stated.